"Aha!": The neural correlates of verbal insight solutions - Aziz-Zadeh, Lisa; Kaplan, Jonas T.; Iacoboni, Marco (Human brain mapping, 2009)
What are the neural correlates of insight solutions? To explore this question we asked participants to perform an anagram task while in the fMRI scanner. Previous research indicates that anagrams are unique in that they can yield both insight and search solutions in expert subjects. Using a single‐trial fMRI paradigm, we utilized the anagram methodology to explore the neural correlates of insight versus search solutions. We used both reaction time measures and subjective reports to classify each trial as a search or insight solution. Data indicate that verbal insight solutions activate a distributed neural network that includes bilateral activation in the insula, the right prefrontal cortex, and the anterior cingulate. These areas are discussed with their possible role in evaluation and metacognition of insight solutions, as well as attention and monitoring during insight. Hum Brain Mapp, 2009. © 2008 Wiley‐Liss, Inc.